Microfluidics and Nanofluidics 2018
DOI: 10.5772/intechopen.72505
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transport and Challenges on Nanofluids Performance

Abstract: Progress in technology and industrial developments demands the efficient and successful energy utilization and its management in a greater extent. Conventional heattransfer fluids (HTFs) such as water, ethylene glycol, oils and other fluids are typically low-efficiency heat dissipation fluids. Thermal management is a key factor in diverse applications where these fluids can be used, such as in automotive, microelectronics, energy storage, medical, and nuclear cooling among others. Furthermore, the miniaturizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 241 publications
(293 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, this aggregation and sedimentation of nanoparticles can significantly reduce the overall heat transfer efficiency of the system and can block the pump or contaminate the heat transfer area. Recent studies have shown that nanofluids tend to agglomerate under harsh operating conditions such as high temperature and pressure [9][10][11]. To manufacture nanofluids with good dispersion stability, researchers have used surfactants as well as nanoparticle coating methods.…”
Section: Nanofluid Preparation For Solar Thermal Applicationsmentioning
confidence: 99%
“…Furthermore, this aggregation and sedimentation of nanoparticles can significantly reduce the overall heat transfer efficiency of the system and can block the pump or contaminate the heat transfer area. Recent studies have shown that nanofluids tend to agglomerate under harsh operating conditions such as high temperature and pressure [9][10][11]. To manufacture nanofluids with good dispersion stability, researchers have used surfactants as well as nanoparticle coating methods.…”
Section: Nanofluid Preparation For Solar Thermal Applicationsmentioning
confidence: 99%
“…Focusing on the agglomeration degree of nanoparticles is essential to choose their effective volume concentration [97]. The increase in nanoparticle agglomeration leads to an increase in sedimentation, decrease in thermal performance, and clogging of flowing paths [98].…”
Section: Sedimentation and Agglomerationmentioning
confidence: 99%
“…The difficulty to achieve a stable suspension with no chemical changes such as pH change or surfactant addition, has been a major challenge [42]. To deal with this issue, homogenization of the suspension is carried out by stirring techniques, such as the ultrasonic bath, magnetic stirrer, and high-pressure homogenizer.…”
Section: Shear Rheology Of Graphene Oxide Suspensionsmentioning
confidence: 99%